Seafloor mapping using high-resolution multibeam backscatter: The Palinuro Seamount (Eastern Tyrrhenian Sea). Issue 5 (19th October 2016) - Innangi, Sara; Passaro, Salvatore; Tonielli, Renato; Milano, Girolamo; Ventura, Guido; Tamburrino, Stella
ABSTRACT: We present a seafloor map of the summit of Palinuro Seamount, an E–W elongated volcanic ridge located in the Eastern Tyrrhenian Sea. The seafloor was mapped using multibeam backscatter and seafloor samples collected between 80 and 1000 m below the sea level. The high-resolution imaging of the Palinuro seafloor was obtained by merging a Digital Terrain Model with a 2.5 m-sized grid and a backscatter mosaic with 2.5 m pixel. The resulting 1:20, 000 scale map includes six main facies recognized based on their backscatter properties. These six facies reflect different lithologies. The Palinuro seafloor map represents a useful tool for morphological and geological studies of the Palinuro volcanic ridge.